Fauna parasitária de capivaras (Hydrochoerus hydrochaeris Linnaeus, 1766) em sistema de criação semi-intensivo, na região sul do Rio Grande do Sul - Wendt, Luciana Welter (2009)
The parasites of capybaras (Hydrochoerus hydrochaeris) in semi-intensive breeding were searched, and examined 39 capybaras (20 young and 19 adults) for ectoparasites, 34 capybaras (13 young and 21 adults) for gastrointestinal helminths. We estimated the parameters of parasitism: prevalence, abundance and mean intensity. Fifty two fecal samples were examined for identification of Eimeria spp. Ticks collected were Amblyomma dubitatum and immature of Amblyomma sp. Among the helminths, four species were identified in young capybaras, with the prevalence and intensity of infection: Capillaria hydrochoeri (46,15% and 11,5 specimens), Hydrochoerisnema anomalobursata (76,92% and 34,2 specimens), Protozoophaga obesa (46,15% and 6,33 specimens) and Monoecocestus hagmanni (23,07% and 1,66 specimens). In adults were found five species: C. hydrochoeri (66,66% and 16,42 specimens), H. anomalobursata (42,85% and 79,88 specimens), P. obesa (100% and 1655,42 specimens), M. hagmanni (14,28% and 38,33 specimens) and Monoecocestus macrobursatum (4,76% and two specimens). Reports of M. hagmanni and M. macrobursatum parasite capybaras in the state of Rio Grande do Sul are unpublished. P. obesa had significantly higher parameters in adult capybaras. In fecal samples, were identified: Eimeria trinidadensis (88,46%) with oocysts that measured 21,02μm (±1,03μm) length and 19,15 (±1,42μm) wide, and Eimeria ichiloensis (79,92%), with oocysts that measured 25,19μm (±1,77μm) length and 19,7μm (±1,3μm) wide. The diversity of founded parasites show the importance of control programs in semi-intensive breeding of capybaras.